Developing Interactive Learning Media Based-Canva in General English at Al-Islam polytechnic - Wahyu Trimastuti; Rudi Hartono; Sri Wahyuni (Universitas Islam Negeri Palopo, 2025)
The development of technology in education has had a significant impact on English Language Teaching (ELT), including General English learning model. In General English learning, teachers are required to use learning models that improve student's interest in learning process. One of learning model to teach General English for students is applying technology media based-Canva. This learning media created by taking the needs which coverage of General English learning material. The aim of this research is to determine the development of learning media and to know students’ responses to the interactive learning media based-Canva in General English. This research applies Research and Development (R & D). The development model in this study uses the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The subjects in this research are 16 undergraduate students of Hospital Administration/23 at Al-Islam Polytechnic. The instruments used in this study were an open questionnaire sheet, material aspect validation sheet, and media aspect validation sheet. The analytical technique used is descriptive qualitative analysis technique and quantitative analysis by finding the average score obtained from the validator’s assessment and looking at the criteria. Validation results from experts of media tell a percentage of 96%, which is included in the very valid category. Meanwhile, validation results from experts of material obtained a percentage of 95%, that is very valid category. Meanwhile, the feasibility of interactive media learning based-Canva, obtained a percentage of 94% with the criteria